2011
DOI: 10.2135/cropsci2010.03.0185
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping of Quantitative Trait Loci Associated with Important Agronomic Traits in the Spring Wheat (Triticum aestivum L.) Cross ‘Louise’ × ‘Penawawa’

Abstract: Understanding the genetic factors underlying agronomic traits in common wheat (Triticum aestivum L.) is essential to making gains from selection during the breeding process. A set of 188 recombinant inbred lines (RILs) from a ‘Louise’ × ‘Penawawa’ mapping population was grown for two crop years at two locations in the Pacific Northwest region of the United States to identify quantitative trait loci (QTL) associated with seedling growth habit, leaf color, plant height, flowering date, maturity date, grain volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
(121 reference statements)
3
14
1
Order By: Relevance
“…The clustering of QTL on chromosome 3B also may be a pleiotropic effect of the grain yield (Carter et al 2011) and grain protein concentration QTL found in the similar region. We detected the well-known negative correlation between grain yield and protein content, although it was moderate in our study.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The clustering of QTL on chromosome 3B also may be a pleiotropic effect of the grain yield (Carter et al 2011) and grain protein concentration QTL found in the similar region. We detected the well-known negative correlation between grain yield and protein content, although it was moderate in our study.…”
Section: Discussionmentioning
confidence: 89%
“…Penawawa also is known to carry a null allele for GBSS on chromosome 4A, which makes it a ''partial-waxy'' wheat . These two parents also contrast for other disease and agronomic traits that are discussed elsewhere (Carter et al 2009(Carter et al , 2011.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, molecular markers such as SSR and DArT have been used to detect QTLs for fusarium head blight (FHB) resistance, which can further be implemented in breeding studies [14]. Since 2007, a number of research studies have been taken to identify QTLs related to yield based on diferent mapping populations such as kernel length, kernel width, spike length, spike number, the grain number of spike, sterile spikelet number per spike, fertile spikelet number per spike, and thousand kernel weight [15][16][17][18][19][20][21][22]. However, the development of molecular markers and their applications in breeding have been relatively diicult in wheat because of its three closely related subgenomes and a large genome size consisted of high amounts (80%) of repetitive sequences.…”
Section: Introductionmentioning
confidence: 99%
“…One of the purposes of the macros is to provide standard errors of genotypic correlation estimates, which would be cumbersome to derive manually by the so‐called delta method based on a fit of an unstructured variance–covariance structure for genotypic effects. The macros are easy to use and are now widely employed by plant breeders (e.g., see Gustafson and de Leon, 2010; Khanal et al, 2011; Carter et al, 2011).…”
mentioning
confidence: 99%